La vulneración del Principio del Interés Superior del Niño y de su Derecho a ser escuchado, en la obligatoriedad de la conferencia del menor alimentista en los procesos de alimentos de la Corte Superior de Justicia de La Libertad - Ocrospoma Gallardo, Giancarlo André (2017)
The objective of this research work is to determine whether the compulsory nature of the food court conference that is currently held in the food court proceedings in the Magistrates' Courts of the Superior Court of Justice of La Libertad violates the principle of the Higher Interest of the Child and his Right to be heard. To this end, international doctrine and norms have been analyzed, fundamentally the one prescribed in the Convention on the Rights of Children, its general observations and recommendations to the States Parties, as well as their adaptation and application in the national legislation embodied in the Political Constitution. of Peru, in the Code of Children and Adolescents and, in the New Protocol of Judicial Participation of Children and Adolescents. In this context, we have proceeded to assess the interpretation that in the processes of food processed before the Superior Court of Justice of La Libertad has been granted to the Principle of the Higher Interest of the Child and to his Right to be heard and; the way in which its application is proceeded. Likewise, through the analysis of the Minutes and observation of the Single Hearings carried out in the food processes, it has been assessed whether the Superior Court of Justice of La Libertad complies with the basic conditions for the observance of the child's right to be heard and the way in which the mandatory appearance of the minor to said audience influences the safeguarding of their psychological integrity, understood as a manifestation of the Principle of the Higher Interest of the Child.